Rozporządzenie eIDAS — nowe ramy prawne w zakresie identyfikacji elektronicznej i usług zaufania w Unii Europejskiej - Siemaszkiewicz, Maria (Wydawnictwo Uniwersytetu Wrocławskiego, 2017)
This article analyses the Electronic Identification and Trust Services eIDAS Regulation which per 1 July 2016 will create a new European legal framework for secure electronic interactions across the European Union EU. The eIDAS Regulation seeks to enhance trust in electronic transactions in the internal EU market by providing a common foundation for secure electronic interactions between citizens, businesses and public authorities, thereby increasing the effectiveness of public and private online services. The article reviews provisions of the eIDAS Regulation related to electronic identification eID, such as removal of existing barriers to the use of the eID in the EU, mutual eID recognition by the EU member states, and interoperability of all national eID schemes. Furthermore, the article focuses on trust services and service providers. Comparing the eIDAS Regulation with its predecessor, the eSignature Directive, the article outlines advantages of the eIDAS Regulation related to the possibility of using trust services as evidence in legal proceedings.
Keywords: rozporządzenie eIDAS; identyfikacja elektroniczna; usługi zaufania; Unia Europejska